Climate and land-use changes coupled with low coverage of protected areas threaten palm species in South Brazilian grasslands - Calambás-Trochez, Licet Fernanda; Velazco, Santiago José Elías; Hoffmann, Pablo Melo; Gurski, Elivelton Marcos; Brum, Fernanda Thiesen; Carlucci, Marcos Bergmann (Perspectives in ecology and conservation, 2021)
[Display omitted] •The palm species of the South Brazilian grasslands are at risk.•In this region, climate and land-use changes increase threats to palm species.•The synergistic effects of these threats increase the risk of extinction of species.•With no future dispersal, palm species are likely to face a drastic range reduction.•Current protected areas in the region are not sufficient to protect palm species. South Brazilian grasslands are at risk due to climate change and activities that convert native vegetation into agricultural lands. We used 12 native palm species as ecological indicators of these ecosystems to evaluate the impact of climate and land-use changes on their geographical distribution. We estimated the potential distribution of species for current and future (year 2050; RCP 4.5 and 8.5) climate and land-use conditions considering two dispersal scenarios. We also assessed the coverage of protected areas (PAs) for current and future species distribution. Our results indicated that the future distribution of all species will decrease under scenarios with no dispersal and increase under scenarios with dispersal; however, a dispersal scenario might be unlikely considering species dispersal ability and the increased pressure on grasslands. A comprehensive strategy is fundamental to ensure species conservation and recovery since the current PAs network covers less than 2% of the current distribution for nine out of the 12 species. Assessing the synergy of trends in climate and land-use changes is essential to improve conservation strategies for these emblematic species.